Killing augmentation of Streptococcus mutans in biofilms and suspensions by 8-Hydroxyquinoline combined with transition-metal cations - Mai Phuong, Nguyen Thi; Ngoc Dao, Nguyen Thi; Lien, Do Ngoc; E. Marquis, Robert (Academia Journal of Biology, 2015)
8-hydroxyquinoline (8HQ) has been used extensively as a chelator of mineral cations and has been found to have a variety of inhibitory effects on the biochemical systems, mainly related to the sequestration of the metal cofactors for enzymes. The bacteria biofilms are notes for resistant to antimicrobial agents reflected by slower rates of killing and higher numbers surviving chanllenge compared with the suspension populations. The Streptococcus mutans strain UA159 mono-organism biofilms on glass slides grown in fed-batch culture were more resistant to 8HQ than those in suspensions. The additions of H2O2 and transition-metal cations greatly increased the sensitivity of 8HQ. Nearly the total killing of cells in biofilm could be achieved in a two-hours expose with as little as 0.001% 8HQ combined with 1 mM iron or copper cations or with 0.01% (2.9 mM) H2O2. The result suggest that 8HQ can be highly toxic for oral streptococci by enhancing the oxidative damage caused by H2O2 and transition-metal cations.